PATOGENISITAS JAMUR ENTOMOPATOGEN Metarhizium anisopliae Metch. TERHADAP KEPINDING TANAH Scotinophara coarctata, Fabricius PADA TANAMAN PADI SAWAH - Marselina A. M. Tular; Max Tulung; James B. Kaligis (COCOS, 2022)
ABSTRACT Rice (Oryza sativa L.) is one of the most important food crops for the Indonesian population because it is a high-carbohydrate staple food. S. coarctata is one of the important pests that attack at all stages of rice plant growth, and is capable of causing losses. One alternative that can be done is by using entomopathogens that are able to control pest attacks, one of which is M. anisopliae. This study was conducted with the aim of knowing the ability of the entomopathogen M. anisopliae to infect S. coarctata. The study was conducted using a completely randomized design (CRD) with 4 treatments and 4 replications, conducted control experiments using density concentration: P1 = 10 6 konidium / ml; P2 = 10 7 conidium/ml; P3 = 10 8 conidium/ml; P0 (control) = Water. Based on the results of observations after application at 2 – 3 DAS, it began to show mycelium growth on the surface of the insect's body which gradually began to change color to olive green. The mortality percentage of S. coarctata against M. anisopliae at a density of 10 8 caused 91%, followed by 10 7 causing 81%; and 10 6 caused 71% mortality at 14 HAS. The results of probit analysis showed that the value of LT50 at a density of 10 6 reached 9 days; 10 7 to 7.7 days; and 10 8 to 7.4 days. Based on the results of the study the percentage mortality is highest indensity of 10 8 konidium/ ml is equal to 91% mortality at 14 DAA. For the value of LT50, namely the death of 50% of the fastest insects found at a density of 10 8 only takes 7.4 days and LC50, which is at a concentration with a density of 10 7.5 conidium/ml. In accordance with the results of the research that has been carried out, it can be suggested that in controllingpests S. coarctata in lowland rice, it is better to use the entomopathogen M. anisopliae and to be applied by farmers, it is necessary to propagate it in the laboratory and then propagated in media ready for use by farmers. Keywords: Rice (Oryza sativa L.), Scotinophara. coarctata, and Metarhizium anisopliae.